Association of PROP (6-n-propylthiouracil) tastes status with sweet and butter taste perception, food preferences and consumption of selected hypertensive Filipino adults - Yap, Alexandra Allyson L. (College of Home Economics, University of the Philippines Diliman, 2019)
The study aimed to assess the PROP taster status and sweet and bitter taste perception to food preferences and dietary consumption of Filipino adults diagnosed with hypertension. The Selected respondents underwent anthropometric assessment and the administration of a food preference checklist and 3-day food record. Sensory evaluation of PROP/NaCl, sugar, and caffeine solutions were also conducted. The population (n=70) was mostly composed of females with mean age of 57.9 years old and classified as preobese. The population was composed of 20% nontasters, 57% medium tasters and 23% super tasters. No significant (p<0.05) correlations were found between PROP taster status and food preferences, and energy and nutrient intakes. Both female and male respondents did not attain the recommended energy intakes of the PDRI. No significant (p>0.05) correlation was found between PROP taster status and sweet and bitter taste intensity, and between sweet and bitter perception and preferences for foods with the same taste modalities. Results of the study show that the PROP taster status and sweet and bitter taste perception of Filipino hypertensive adults were different from those observed with normotensive Filipino adults which may be attributed to factors such as hypertension medications and nutritional interventions.